The Clinical Application of a Self-developed Gasless Laparoendoscopic Operation Field Formation Device on Patients Undergoing Cholecystectomy. Issue 5 (October 2020) - Hu, Hai; Zhao, Gang; Zhang, Kai; Cai, Hao; Jiang, Zhaoyan; Huang, Anhua; Cai, Jingli; Xu, Anan; Li, Haidong; He, Chuanqi
Abstract : Background: We have designed a new gasless laparoscopic operation field formation (LOFF) device for cholecystectomy which was successfully tested on animal model. The goal of this study is to investigate the feasibility, safety and effectiveness of this LOFF device on patients undergoing cholecystectomy. Methods: Patients with cholecystolithiasis or gallbladder polyps who underwent single port cholecystectomy from June 2015 to May 2016 were retrospectively reviewed. Either the LOFF-assisted laparoendoscopic single-port surgery (LESS) (LOFF-LESS) or the traditional LESS was performed. Operation time, intraoperative bleeding, postoperative hospital stay, surgical complications, incision pain score, shoulder and back pain and cosmetic satisfaction were compared. Results: A total of 186 patients were included in this study, with 79 in the LOFF-LESS group and 107 in the LESS group. There was no significant difference between LOFF-LESS group and LESS group in operation field establishment time, cholecystectomy time, intraoperative bleeding, postoperative hospital stay, incision pain and cosmetic satisfaction. A lower intraoperative arterial carbon dioxide pressure was documented in the LOFF-LESS group ( P <0.01). The incidence of postoperative shoulder and back pain was significantly lower in LOFF-LESS group ( P <0.01). Conclusion: LOFF-LESS has comparable benefits of traditional LESS; it deceases incidence of pneumoperitoneum related complications as well. Abstract : Supplemental Digital Content is available in the text.